The expansion of exotic Chinook salmon (Oncorhynchus tshawytscha) in the extreme south of Patagonia: an environmental DNA approach - Nardi, Cristina Fernanda (2019)
The ability to detect species at low densities, greatly improves the success of management action on alien invasive species and decreases their possible impact on ecosystems. In the last two decades, exotic Chinook salmon (Oncorhynchus tshawytscha) have established populations in both Pacific and Atlantic river basins of Patagonia. The last established populations have been reported in the extreme south of Patagonia, on the island of Tierra del Fuego (TDF). The relatively recent appearance of Chinook salmon in TDF and the great phenotypic plasticity of this species, make it necessary to study their distribution and expansion as soon as possible, since they have the potential to negatively impact on native ecosystems. With the objective of knowing the current distribution status of exotic Chinook salmon in TDF, we optimized and implemented a detection method based on environmental DNA (eDNA). First, we designed Chinook salmon-specific primers, with no cross-amplification, using DNA from other species that are living at the same environment. Second, we validated the primers in situ by detecting Chinook salmon DNA from natural environments at the same time that we performed a conventional survey using an electrofishing survey method. Finally, we collected water samples from 10 river basins and one estuary within TDF and one river basin from Isla de los Estados (IE) and performed single-species real-time PCR assays. We were able to detect Chinook salmon DNA from 5 basins and from the estuary in TDF. These eDNA-based results allowed us to confirm the expansion of exotic Chinook salmon since they were first reported in TDF.